(untitled) (Bulletin of Armenian Libraries, 2023)
The presentation is a general introduction to the historical development and the current state of the “publishing mission” of the Cilician Catholicossate. The presentation consists of five complementary parts: introduction, departments (we will describe the main cultural book institutions), results, publishing funds and our upcoming work. Let us recall that our eparchies are also institutions that carry out their publishing activities in the same spirit as the Cilician Catholicossate, but they are not the subject of this report. Extensive information on this issue can be found in the journal “ASK,” published by the Catholicossate, and analytical summaries can be found in a book dedicated to the 25th anniversary of the reign of Supreme Patriarch Aram A.